Analisis Intensifikasi Pajak Restoran terhadap Peningkatan Penerimaan Pajak Daerah di DKI Jakarta Tahun 2020 – 2022 Ana Chaerunisyah 1 , Ambarwati 2* , Nissa Oktiva 3 - Chaerunisyah, Ana; Ambarwati, Ambarwati; Oktiva, Nissa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Restaurant Tax is a tax on services provided by restaurants. The phenomenon in this research is the Restaurant Tax Revenue that has not yet reached the specified target due to the Covid-19 pandemic. Taxpayers have faced difficulties in paying taxes, resulting in reduced income collection. Many registered Restaurant Tax taxpayers do not meet their Tax Payment Obligations. Furthermore, public awareness of taxation remains limited. This research aims to investigate and analyze the intensification of restaurant tax collection and its impact on the increase in Regional Tax Revenue in DKI Jakarta. It also explores the obstacles faced and the efforts made by the Regional Revenue Agency (BAPENDA) of DKI Jakarta to boost Regional Tax Revenue. This study employs a descriptive qualitative research method, collecting data through Observation, Interviews, and Documentation at the BAPENDA DKI Jakarta Office. The research findings indicate that the intensification of Restaurant Tax Collection for the increase in Regional Tax Revenue has not been successful. This is evident from the failure to achieve the revenue target and realization of Restaurant Tax Collection in DKI Jakarta from 2020 to 2022. This situation can be attributed to the Covid-19 pandemic and inadequate Tax Payment outreach efforts. BAPENDA DKI Jakarta’s initiatives include conducting Inspections, Providing Socialization and Education, Improving Service Quality, Implementing Tax Collection for Restaurant Tax taxpayers and Offering Extended Time for Restaurant Tax Calculations.